2009
DOI: 10.1158/0008-5472.can-08-0506
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Decreases with Mutations of Melanosomal Regulatory Genes

Abstract: Whereas resistance to chemotherapy has long impeded effective treatment of metastatic melanoma, the mechanistic basis of this resistance remains unknown. One possible mechanism of drug resistance is alteration of intracellular drug distribution either by drug efflux or sequestration into intracellular organelles. Melanomas, as well as primary melanocytes from which they arise, have intracellular organelles, called melanosomes, wherein the synthesis and storage of the pigment melanin takes place. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…The data here indicate that melanomas can be protected from apoptosis by melanosomal sequestration of treatment agents, consistent with our and other groups' previous findings that melanosome function plays a role in melanoma treatment resistance (13,(27)(28)(29)(30)(31). Gottesman and colleagues (29) have shown that chemosensitivity is independent of melanoma pigment content, consistent with a melanosome function alternative to that of melanin synthesis (e.g., sequestration) influencing chemosensitivity.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The data here indicate that melanomas can be protected from apoptosis by melanosomal sequestration of treatment agents, consistent with our and other groups' previous findings that melanosome function plays a role in melanoma treatment resistance (13,(27)(28)(29)(30)(31). Gottesman and colleagues (29) have shown that chemosensitivity is independent of melanoma pigment content, consistent with a melanosome function alternative to that of melanin synthesis (e.g., sequestration) influencing chemosensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…We previously demonstrated that primary mouse melanocytes with mutations in Vps33a or Cno had aberrant melanosome formation and increased sensitivity to cis-platin (cDDP) compared with melanocytes from the congenic parental mouse strains (13). To assess whether depletion of VPS33A or CNO proteins in human melanoma cells affects drug sensitivity, we established stable isogenic cell lines by selecting clones of the pigmented human melanoma cell line MNT-1 after transduction with shRNA targeted to either VPS33A or CNO.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations